2018
DOI: 10.1111/jomf.12545
|View full text |Cite
|
Sign up to set email alerts
|

Paternity Leave and Parental Relationships: Variations by Gender and Mothers' Work Statuses

Abstract: Objective: This study examines the associations between paternity leave and parents' reports of relationship satisfaction and relationship conflict and whether the associations vary by parent gender and mothers' work statuses. Background: Paternity leave research in the United States has focused on implications for father involvement, but paternity leave may also help to strengthen parental relationships by promoting a more equitable division of domestic labor. Given gender gaps in child care, the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
2
29
3
Order By: Relevance
“…Our expectation that equally shared parental leave would be associated with parents’ couple relationship satisfaction, was met for fathers but not for mothers. This finding is in contrast to Petts and Knoester’s (2019) finding that fathers’ parental leave taking and length of time on parental leave was associated with perceived couple relationship satisfaction only in mothers, but not in fathers. Maybe the substantive differences between the United States (Petts & Knoester, 2019) and Sweden in contextual prerequisites for paid parental leave can bring some understanding to the contrasting findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our expectation that equally shared parental leave would be associated with parents’ couple relationship satisfaction, was met for fathers but not for mothers. This finding is in contrast to Petts and Knoester’s (2019) finding that fathers’ parental leave taking and length of time on parental leave was associated with perceived couple relationship satisfaction only in mothers, but not in fathers. Maybe the substantive differences between the United States (Petts & Knoester, 2019) and Sweden in contextual prerequisites for paid parental leave can bring some understanding to the contrasting findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Fathers’ parental leave taking has been discussed as a sign of a deeper commitment to family life (Petts & Knoester, 2019), yet parents’ experiences of egalitarian parental roles during equally shared parental leave were not fully reflected in the family dynamics as we hypothesized. Our expectation that equally shared parental leave would be associated with parents’ couple relationship satisfaction, was met for fathers but not for mothers.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A sense of unfairness with the division of household labor and child care within their partnerships, and a decline in time together alone, may be key reasons for the decline in relationship quality among parents (Dew & Wilcox, ; Schieman, Ruppanner, & Milkie, ). Fathers' taking paternity leave, which presumably helps to reduce the sense of unfairness with the division of labor, was positively associated with both parents' reports of relationship satisfaction; and length of paternity leave was positively associated with mothers' (but not fathers') reports of relationship satisfaction (Petts & Knoester, ). Gender differences in the effects of the transition to parenthood on perceived relationship quality were mixed (Don & Mickelson, ; Holmes, Sasaki, & Hazen, ; Keizer & Schenk, ), which could be attributed to differences in sample characteristics.…”
Section: A Life Course Perspectivementioning
confidence: 99%
“…Studies have not uniformly found that longer periods of paid leave are associated with higher levels of father involvement with children. U.S. studies have shown that fathers who take longer periods of paternity leave are more engaged with their young children (Petts & Knoester, ; Pragg & Knoester, ), and their partners report higher couple relationship satisfaction (Petts & Knoester, ). A large‐scale study using data from the 2005 European Working Conditions Survey found that men's utilization of parental leave was associated with more frequent involvement in child care irrespective of the duration of the leave (Meil, ).…”
Section: Significant Developmentsmentioning
confidence: 99%